A Regression Analysis Approach to Van Everdingen-Hurst Dimensionless Water Influx Variables for Infinite and Finite Aquifers - Muhammad Taufiq Fathaddin; Yarra Sutadiwiria; Taufan Marhaendrajana; Sonny Irawan; Onnie Ridaliani Prapansya; Asri Nugrahanti (Testing Center for Oil and Gas LEMIGAS, 2024)
Water influx calculations have relied on accurate values of the Van Everdingen-Hurst WeD dimensionless variables. For programming and hand calculators, equations are needed to determine WeD. Previous models provide equations for WeD calculations for infinite aquifer cases. This paper presents two sets of regression equations that are simple to apply to obtain accurate values of WeD for either infinite or finite aquifer cases. The proposed equations have good agreement with the Van Everdingen-Hurst method with an average difference of 0.77% and 1.18% for the cases of infinite aquifer and finite aquifer, respectively